Assessment of Drought Impacts in the North River Basin - Hassanzay, Fazalhaq; Reshteen, Sediqullah; Rahmatzai, Asadullah (Journal of Natural Sciences – Kabul University, 2026)
Variations in meteorological elements, particularly precipitation, are among the most essential characteristics of atmospheric and hydrological systems. Drought, as one of the most hazardous natural phenomena, can cause extensive negative impacts on society and the environment depending on its intensity and duration; therefore, its assessment is of great importance. This study aims to analyze drought conditions in the North River Basin using statistical approaches. The Standardized Precipitation Index (SPI) was applied, and the Normal and Log-Normal SPI results were compared. The analysis was based on precipitation data from 13 stations spanning 1979–2022. The results indicate that eight moderate drought events and one severe drought event occurred during the study period. Furthermore, the return periods of mild, severe, and extremely severe droughts were estimated at approximately 2–3, 10–15, and 20–25 years, respectively. In addition, a notable decrease in precipitation associated with climate change has been observed in the basin.